The Integration Project Among White Teachers and Racial/Ethnic Minority Youth: Understanding Bias in School Practice. Issue 3 (3rd July 2017) - Fergus, Edward
Abstract : In 1954, the Supreme Court ruled schools in the United States needed to desegregate and begin integration. The decision was a radical departure from the facilities argument initially presented; it added the issue that the segregation of Black students was having a deleterious effect on their self-concept. Many scholars argue the integration has not been sustained (Orfield and Frankenberg, 2014); in fact, a recent report highlights Black, Latino and Native American students are less integrated with White and Asian students than in 1954 (Orfield and Frankenberg, 2014). However the Brown decision set forth another integration project – the integration of White practitioners (i.e., teachers and principals) with Black, Latino and Native American student populations! This article brings together an array of social interaction research that articulates the complexity of this integration project. More specifically, the article focuses on demographic patterns of intimate interactions (i.e., friendship networks, interracial marriage), research studies that document race-based ideas of learning and achievement; the presence of "passive" lowered expectations occurring through interactions such as stereotype threat (Steele and Aronson, 1995) and racial/ethnic microaggressions (Wing Sue, 2010) and "active" lowered expectations through school structures such as curriculum (Anyon, 1983) and resource allocation (Campaign for Fiscal Equity v. NYS, 2003).